Investigation of regression rate end-burning typed hybrid rocket motor - Sabri, Muhammad Ezamuddin Ezzad; Azami, Muhammad Hanafi; Abdullah, Nur Azam; Nordin, Norhuda Hidayah (Aeronautical and Astronautical Society of the Republic of China, 2023)
Hybrid rocket motor has a critical weakness that impacts performance: low regression rate. Due to this, extensive investigation has been done on end-burning hybrid rocket motors to enhance the regression rate. Experimental works were conducted on the end-burning hybrid rocket motor. The present investigation is focused on single port hybrid rocket motor, paraffin wax, and gas oxygen as the fuel and oxidiser, respectively. The results show that combustion occurs only at the fuel end in end-burning mode, which ensures that the oxidiser-to-fuel ratio does not fluctuate, enhancing the motor's performance. Hybrid rocket motor performance has been evaluated by calculating the regression rate, thrust and specific impulses. From this study, an end-burning hybrid rocket motor has a 33% less regression rate but around a 50% increase in thrust and specific impulse compared to a conventional hybrid rocket motor. The low regression is due to the small initial combustion area. Mass flux is the more prominent factor in increasing the regression rate and thrust of the end-burning hybrid rocket motor compared to the fuel length. Further improvement to the design of the hybrid rocket motor can maximise the potential of the end-burning mode.